Urbanos sim, modernos talvez : notas sobre a cultura de morar em Caxias do Sul - Moraes, Erinton Aver (My University, 2020)
The history of Italian immigrants and their descendants, in Caxias do Sul and region, has been told in countless ways and from different epistemological shades. This research seeks to approach it from the point of view of the architecture of their houses and, more specifically, the culture of living. The option for this object of investigation, the house, occurs because this is a privileged place for the study of intimacy, able to expose habits and customs of its residents, revealing aspects of the local culture. The choice of the house as object of study therefore allows a double approach; one concerns the history of its inhabitants and their habits, the motto of this investigation; the other, no less important, refers to the localized and peripheral examination of Brazilian architecture, thus contributing to the apprehension and comprehension of the totality of this production. In relation to this last aspect, this text points in the opposite direction to that which reinforces a unitary view, erasing differences, exalting dominant and dominating forms and dissimulating diversity.
A história dos imigrantes italianos e seus descendentes, em Caxias do Sul e região, tem sido contada de inúmeras formas e a partir de diferentes matizes epistemológicos. Essa pesquisa procura abordá-la do ponto de vista da arquitetura de suas casas e, mais especificamente, da cultura de morar. A opção por esse objeto de investigação, a casa, ocorre porque essa é um lugar privilegiado para o estudo da intimidade, capaz de expor hábitos e costumes dos seus moradores, revelando aspectos da cultura local. A escolha da casa como objeto de estudo permite, portanto, dupla abordagem; uma diz respeito à história de seus habitantes e seus hábitos, mote dessa investigação; a outra, não menos importante, se refere ao exame localizado e periférico da arquitetura brasileira, contribuindo, dessa forma, para a apreensão e compreensão da totalidade dessa produção. Em relação a esse último aspecto, esse texto aponta na direção oposta àquela que reforça um olhar unitário, apagando diferenças, exaltando as formas dominantes e dominadoras e dissimulando a diversidade.
Keywords: Cultura - Caxias do Sul (RS); Habitações - Caxias do Sul (RS); Arquitetura de habitação; Italianos; Culture - Caxias do Sul (Brazil); Dwellings - Caxias do Sul (Brazil); Housing architecture; Italians